African Cultural Values and Corruption in Nigeria: New Insights - Terngu Sylvanus Nomishan; Oryina Joel Andzenge; Alegbejo Noah Kolawole; Peter Luke Oyigebe (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
African cultural values connote core principles and ideals that maintains good, right, fair and just in African societies. This culture is developed over a long period of time, preserved and promoted by all members of a given group or society. Corruption as a phenomenon on the other hand has been variously described as a societal vice. Though research shows that some levels of corruption exist in almost every human society, it is over accommodated in some societies or nations and as such it has notoriously continued to destroy such societies/nations. This is particular to a number of African nations, with Nigeria being among (if not) the worse corrupt nation(s) in the continent. It is not difficult to understand that the value placed on corruption in Nigeria is synonymous to the way cultural values are cherished by people in some nations of the world. In view of this, there is a serious and immediate need to educate the Nigerian public about the consequences of developing a culture of corruption in the country. It seems that some Nigerians take corruption to be a normal way of life, thereby, equating the vice to acceptable cultural values. Today, many Nigerians are not interested in developing and/or preserving amiable cultural values for the nation. Rather, more attention is focus on the promotion of corrupt practices that enables the destruction of even the good cultural values of the nation that were left behind by our forefathers. Therefore, this paper seeks to unmask the importance of developing and preserving good African cultural values that will guarantee unity, patriotism, social cohesion and sustainable development in Nigeria.